Knowledge, attitude, and practices on COVID-19 prevention and diagnosis among medical workers in the radiology department: A multicenter cross-sectional study in China - Sun, Qiyuan; Yu, Chunyan; Zheng, Zhedong; Wu, Qiong; Zhang, Jian; Jiang, Peng; Liu, Ying (Frontiers in Public Health, 2023)
Objective: The aim of this study was to investigate the knowledge, attitude, and practice (KAP) of medical workers in the radiology department toward the prevention and diagnosis of COVID-19. Methods: This multicenter cross-sectional study was conducted among medical workers in the radiology department of 17 hospitals between March and June 2022. Results: A total of 324 medical workers were enrolled. The mean knowledge scores were 15.3±3.4 (out of 23), attitude scores were 31.1±5.6 (range 8-40), and practice scores were 35.1±4.4 (range 8-40). Positive attitudes (OR=1.235, 95%CI: 1.162-1.311, P<0.001) and aged 41-50 years were independently associated with higher practice scores. Those with the better practice were more likely to be older (OR=2.603, 95%CI: 1.242-5.452, P=0.011), nurses (OR=2.274, 95%CI: 1.210-4.272, P=0.011) and with junior/intermediary/vice-senior title (OR=2.326, 95%CI: 1.030-5.255, P=0.042; OR=2.847, 95%CI: 1.226-6.606, P=0.015; OR=4.547, 95%CI: 1.806-11.452, P=0.001, respectively). Subgroup analysis revealed significant differences in knowledge between technicians and physicians and nurses and between staff working in tertiary hospitals and non-tertiary hospitals. Knowledge is positively correlated with attitude (β=0.54, p < 0.001), and attitude is positively correlated with practice (β=0.37, p < 0.001). Attitudes significantly mediated the association between knowledge and practice (β = 0.119, p < 0.001). Conclusion: The radiology medical workers showed moderate knowledge but good attitudes and practices of prevention and diagnosis of COVID-19. Attitudes were found to be positively associated with better practices of prevention and diagnosis of COVID-19. Attitudes significantly mediated the association between knowledge and practice.